2022
DOI: 10.3390/ijerph19042023
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Education during the SARS-CoV-2 Pandemic: Assessment of Students’ Satisfaction with e-Learning Environment

Abstract: The disease caused by the SARS-CoV-2 coronavirus led to the disruption of normality with respect to education, public healthcare and new technologies. Education is a fundamental pillar to increase the knowledge and morale of people. However, due to the lockdown implemented to protect the population from an infection of unknown aetiology, the education system decided to switch from face-to-face education to virtual education. This modality has affected the teaching–learning process in the Degree of Nursing, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
1
1
3
Order By: Relevance
“…Furthermore, in an integrative review on nursing students' satisfaction with e-learning during the pandemic, it was shown that they had high satisfaction levels during their learning experiences [23]. On the other hand, the current study contradicts findings with other studies, which showed students are dissatisfied with online learning [24]. Another study conducted in Iran showed that more than 88% of nursing students were satisfied with online learning [25]; furthermore, findings from the study conducted in Iran showed that universities were not completely successful in satisfying students in online learning [26].…”
Section: Discussioncontrasting
confidence: 96%
“…Furthermore, in an integrative review on nursing students' satisfaction with e-learning during the pandemic, it was shown that they had high satisfaction levels during their learning experiences [23]. On the other hand, the current study contradicts findings with other studies, which showed students are dissatisfied with online learning [24]. Another study conducted in Iran showed that more than 88% of nursing students were satisfied with online learning [25]; furthermore, findings from the study conducted in Iran showed that universities were not completely successful in satisfying students in online learning [26].…”
Section: Discussioncontrasting
confidence: 96%
“…41 However, a cross-sectional study of 400 nursing students found that educators were struggling with online learning, reducing student satisfaction. 42 Hence, when educators manage online learning easily, students may perceive their lessons as more engaging than traditional ones. Consequently, educators could try to become more proficient at online learning and incorporate the assets of it into traditional lessons (blended learning).…”
Section: Learning Environmentmentioning
confidence: 99%
“…Blant intensivsykepleiestudentene som enten delvis, eller ikke i det hele tatt, har oppnådd sine laeringsmål i teoretiske emner, opplevde 72 prosent at pandemien har redusert deres motivasjon til å gjennomføre studiet. Både redusert motivasjon og lavt laeringsutbytte, som følge av overgang til digital undervisning, er gjennomgående i resultatene, noe som samsvarer med flere internasjonale studier (5,9,10,24,25). Tradisjonelt har intensivsykepleiestudentenes undervisning foregått i klasserom med fysisk tilstedevaerelse, og digital undervisning var en lite brukt laeringsplattform frem til vårsemesteret 2020.…”
Section: Teoretisk Laeringsutbytteunclassified
“…Overgang til digitale laeringsplattformer førte til at studentene ble demotivert fordi det ble annerledes enn det de var vant til, og motivasjon er en av de viktigste faktorene for å oppnå laeringsmål (8). Videre viste en spansk tverrsnittstudie av siste års sykepleiestudenter at overgang til digital undervisning medførte lav tilfredshet, hvor 76-84,5 prosent oppgav misnøye med innhold og presentasjon av undervisningen (9). En systematisk oversiktsartikkel, med 16 studier av sykepleie-og legestudenter, viste at simuleringstrening utført digitalt gav et godt laeringsutbytte og er et alternativ til klinisk praksis.…”
unclassified